Ionic Liquid‐Assisted Synthesis of TiO2–Carbon Hybrid Nanostructures for Lithium‐Ion Batteries. (18th January 2016) - Cheng, Yanhua; Chen, Zheng; Wu, Haobin; Zhu, Meifang; Lu, Yunfeng
Abstract : Building nanocomposite architectures based on nanocarbon materials (such as carbon nanotubes and graphene nanosheets) and metal‐oxide nanoparticles is of great interests for electrochemical energy storage. Here, an ionic‐liquid‐assisted strategy is presented to mediate the in situ growth of TiO2 nanocrystals with controlled size on carbon nanotubes and graphene, and also reduce the modified carbon supports to recover the graphitic structure simultaneously. The as‐prepared nanocomposites exhibit a highly porous and robust structure with intimate coupling between TiO2 nanocrystals and carbon supports, which offers facile ion and electron transport pathway as well as high mechanical stability. When evaluated as electrode materials for lithium‐ion batteries, the nanocomposites manifest high specific capacity, long cycling lifetime, and excellent rate capability, showing their promising application in high‐performance energy storage devices. Abstract : A one‐step ionic‐liquid (IL)‐assisted approach is developed to fabricate TiO2 –carbon nanocomposites for battery anodes. The IL mediates the uniform growth of TiO2 nanocrystals with controlled size on nanocarbons with intimate contact and in situ reduces the modified carbon supports to recover the graphitic structure. This leads to nanocomposites with high specific capacity, long cycling lifetime, and excellent rate capability.